PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN ”LNY SKINCARE” - Siti Maesaroh (Journal Of Communication Education, 2023)
The emergence of consumer dissatisfaction is indicated by customer complaints after having beauty treatments at "LNY Skincare". The purpose of this study is to determine the effect of service quality and price on Leny Skincare customer loyalty. The method used in this research is a quantitative method. The population in this study are "LNY Skincare Citra Raya" customers who perform maintenance, totalling 120 consumers, then the sample in this study is determined using the Slovin formula with a total of 92 respondents. The data collection technique used is the questionnaire method at the beauty clinic "LNY Skincare Citra Raya". Methods of data analysis using descriptive analysis namely validity test, reliability test, classical assumption test, correlation test, coefficient of determination test, regression test, and hypothesis test using SPSS version 29.0. The results of the correlation test of service quality and price on customer loyalty obtained 0.858, which means a very strong relationship simultaneously. Based on the results of the coefficient of determination of service quality and price on customer loyalty, an R2 value of 0.737 means that the coefficient of determination of service quality and price variables simultaneously influences customer loyalty by 73.7%. Based on the results of the t-test, it can be concluded that service quality and price have a partial effect on customer loyalty. Then from the results of the F test, it can be concluded that there is a significant simultaneous effect between service quality and price variables on customer loyalty.